An ordinance concerning cattle, fences of plantations and other objects of the rural police, within the city of New-Orleans, Art. 16 (31 July, 1828) - (:unkn) unknown (General Publisher, 1828)
Whoever shall fire a gun or other kind of fire-arms near any other inhabited place ; whoever shall fire at pigeons, or shall kill or wound any domestic animal, while hunting or fowling on another person's land, shall, in every such case, be fined from twenty-five to fifty dollars, besides his being liable for damages to the party concerned, and even to prosecution, if cause be found."
--
Keywords: DISCHARGE